Mary Emerson. Greek Sanctuaries and Temple Architecture. An Introduction - Spawforth, Tony (Journal of Greek Archaeology, 2019)
In her preface the author explains what is new in this second edition: chapters on Paestum and the temple of Zeus at Akragas, commentary on architectural sculpture, and an expanded bibliography. The book is avowedly introductory, the emphasis is on buildings, and a glossary explains the technical terms used in the text, which the reader had best get used to since – as Emerson says – they litter the further reading. Other than the new sites (above), the content focuses on Delphi, Olympia, Athens (Acropolis and the Hephaisteion) and Bassae. These being the core sites (‘classics’ as Emerson says) for the study of Greek sacred architecture, this is a sensible approach for an introduction (one might quibble about the omission of any structures specifically built for initiation rites from the Archaic and Classical periods, the timespan to which the book confines itself).